Postoperative dysesthesia after PVCR without anterior support applied in Yang's type A severe spinal kyphoscoliosis - Wu, Hangqin; Ding, Jie; Yang, Junlin; Sui, Wenyuan (Frontiers in Surgery, 2023)
Backgrounds The incidence and characteristics of postoperative dysesthesia (POD) have not been reported for posterior vertebral column resection (PVCR) in the treatment of severe spinal kyphoscoliosis. Objective The objective of the study is to investigate the incidence and characteristics of POD in PVCR without anterior support applied in Yang's type A severe spinal kyphoscoliosis. Material and methods From August 2010 to December 2019, 167 patients diagnosed with Yang's type A severe spinal kyphoscoliosis who underwent PVCR without anterior support applied were retrospectively reviewed. All the patients were monitored using five modes of intraoperative multimodal neurophysiological monitoring. Neuromonitoring data, radiographic parameters, and neurological complications were reviewed and analyzed. The incidence and characteristics of POD were further summarized. POD was defined as dysesthetic pain or burning dysesthesia which could be caused by spinal cord kinking or dorsal root ganglion (DRG) injury but with no motor deficits. Results PVCR without anterior support was successfully conducted in all 167 patients. Intraoperative monitoring events occurred in five patients. One out of these five patients showed postoperative spinal cord injury (Frankel level C) but completely recovered within 9 months postoperation (Frankel level E). The number of levels and osteotomy space for vertebra resection were 1.28 and 3.6 cm, respectively. POD was confirmed in three patients (3/167, 1.8%), characterized as kyphosis with the apex vertebrae in T12 with the kyphotic Cobb angles of 100°, 115°, and 122°, respectively. The osteotomy space of vertebra resection in these three patients were 3.9, 3.8, and 4.2 cm, respectively. After the treatment by drug administration, they reported pain relief for 12–36 days. The pain gradually moved to the distal end of a proper DRG innervated region near the end. Conclusions In this study, the incidence rate of POD in Yang's type A severe spinal kyphoscoliosis patients who underwent PVCR without anterior support applied was 1.8% (3/167). Evoked potential monitoring could not detect the occurrence of POD. POD in Yang's type A severe spinal kyphoscoliosis after PVCR could be ascribed to spinal cord kinking and DRG injury.